SOFTENED WOOL AND OTHER FIBERS MIXTURE TECHNOLOGICAL PROPERTIES (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2025)
This in the article softened sheep wool other fibers — viscose , polyester and natural fibers with mixed in the state technological properties studied . Mixed in the composition of fibers flexibility , one diversity , physical-mechanical connection level and flexibility analysis The research was conducted results mixture fibrous products working optimal proportions in production definition , product quality increase and energy economical technologies in use important importance has .